Win or Lose? Listen to a Martingale! - Paranjape, K.H. (Springer Link, 2019)
The author did not learn probability theory properly when it was taught to him as an undergraduate. However, now that he has to teach, it has become a fascination. The problem stated below was given to second year students of the IISER BS-MS programme as an examination question; they answered it in interesting ways. An earlier article in Resonance [1] also talks about martingales.
Keywords: Probability theory; Undergraduate; Fascination